Getting Choice Right : Ensuring Equity and Efficiency in Education Policy - Loveless, Tom, 1954-; Betts, Julian R. (Book collections on Project MUSE., 2005)
"Analyzes the potential costs and benefits of school choice and discusses policy mechanisms that would maximize its benefits while mitigating its social costs, specifically in terms of racial and religious issues and the promotion of civic values"--Provided by publisher.